Pembelajaran Tari Hadrah di SMAN 1 Way Tenong Kabupaten Lampung Barat - Rido Amalgrah; riyan Hidayatullah; susi Wendhaningsih (Jurnal Seni dan Pembelajaran, 2018)
The problem of the research was how the process of Hadrah dance learning. The aim of this study was to describe the process and the result of Hadrah dance learning. The method used was qualitative descriptive design. The data sources were taken from the teacher and whole students in class XI IPA 3. The techniques in collecting the data were observation, interview, questionarre, documentation and scoring instrument. The data analyzing techniques were reducting the data, presenting the data, taking the conclusion, and verifying. The steps in learning Hadrah dance in SMAN1 Waytenong were; preparing the students, warming up, preparing the materials, demonstrating, asking the students to practice it, and evaluating. The scoring of learning result can be seen from the aspects of wiraga, wirama, wirasa,wirupa. The result of learning shows that the Hadrah dance learning was implied in good category, with average score is 77; category